PENGARUH PENGHAPUSAN AMBANG BATAS PENCALONAN PRESIDEN (PRESIDENTIAL THRESHOLD) TERHADAP SISTEM PEMILU STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 62/PUU-XXII/2024 - Jatmiko, Krisno; Nurfransiska, Ferika; Sutiyani, Sutiyani; Putra, Vingky Dwi (Gapenas Publisher, 2025)
This research is motivated by the existence of a provision for the threshold for presidential candidacy in Article 222 of Law Number 7 of 2017 which regulates the minimum requirement of 20% of the House of Representatives seats or 25% of the national valid votes for political parties to nominate the president. This provision is considered to limit the participation of small parties and cause electoral injustice. The Constitutional Court, which previously consistently rejected the testing of Article 222, through Decision Number 62/PUU-XXII/2024 finally canceled the article because it was considered to violate the principle of people's sovereignty and cause intolerable political inequality. This research uses a normative juridical method with a legislative, case, and conceptual approach, as well as analyzing primary and secondary legal materials. The results of the study show that the Constitutional Court can test norms in the realm of open legal policy if it is proven to be contrary to the constitution. Although only as a negative legislator, the Court also provides normative recommendations as a guide for the House of Representatives to draft replacement regulations, such as the elimination of vote-based or seat-based thresholds, as well as involving small parties in the formation of laws. This ruling creates a legal vacuum that must be immediately responded to by lawmakers to maintain legal certainty ahead of the 2029 election. This research emphasizes the importance of consistency in the legal reasoning of the Constitutional Court and the need for public involvement in the formulation of new norms so that electoral democracy in Indonesia is maintained.